Peritoneal and Pulmonary Tuberculosis in a Postpartum Female with Elevated Cancer Antigen 125 and Ascites. (26th October 2022) - Lavrynenko, Olga; Baireddy, Moulika; Bodepudi, Srilekha; Santos, Hector; Cortez, James; Zemlianitsyna, Olga; Sanchez, Fernando
Abstract : Background . Peritoneal tuberculosis is a rare form of extrapulmonary tuberculosis and presents a challenging diagnosis because of its nonspecific clinical manifestations. Peritoneal TB mimics other pathologies, including abdominal carcinomatosis, especially when the patient presents with ascites and an elevated cancer antigen (CA)-125 levels. Case Presentation . A postpartum 20-year-old Hispanic female recently discharged after transverse cesarean surgery, presented to the ER with fever, chills, edema, abdominal distension, nausea, and vomiting. The patient was febrile, tachycardic, and hypotensive. Chest X-ray demonstrated alveolar and interstitial consolidations; chest CT revealed tree-in-bud opacities in the right lower lobe, suggestive of atypical (TB)/fungal infection. CT of the abdomen and pelvis demonstrated ascites, omental thickening, peritoneal thickening, and mesenteric adenopathy, suggestive of carcinomatosis. She was admitted with a presumed diagnosis of sepsis secondary to pneumonia and started empirically on broad-spectrum antibiotics without clinical improvement. A battery of oncology markers was ordered and revealed a mildly elevated cancer antigen (CA)-125. Diagnostic paracentesis showed lymphocytic predominance with positive mycobacteria PCR, elevated adenosine deaminase (ADA), and no malignant cells. Subsequently, the sputum acid-fast bacilli (AFB) stain returned positive for tuberculosis, confirming the diagnosis of pulmonary tuberculosis. A peritoneal biopsy was obtained and demonstrated caseating granulomas consistent with peritoneal tuberculosis. The patient was started on standard antituberculosis therapy with clinical improvement. Conclusions . This case highlights the need for a high-level of suspicion for peritoneal tuberculosis in a patient with pulmonary tuberculosis who presents with intra-abdominal ascites, omental thickening, peritoneal thickening, and mesenteric lymphadenopathy, despite the presence of an elevated CA-125 level.